COMPARISON OF KIDNEY DISEASE PREVALENCE IN TYPE 2 DIABETIC PEOPLE AND NON-DIABETIC PEOPLE. - Ankit Abhishek; Ajay Kumar Sinha; Santosh Kumar (Student's Journal of Health Research, 2023)
Aim: The key motive of this research is to evaluate the frequency of kidney diseases in subjects with type 2 diabetes vs. nondiabetic patients. For the estimation of the similarity between the relation of normoalbuminuria and microalbuminuria with type 2 diabetes and on which point renal diseases different percentage of the patient of type 2 diabetes lies. Materials and Methods: This was a cross-sectional study of 200 cases organized at a tertiary care center in Bihar, India. The study was performed for 24 months, and all the patients were 20-80 years of age. Age, body mass, height, BMI, fasting blood sugar, random blood sugar, and duration of diabetes of patients were recorded. Results: It was evaluated that the incidence of kidney diseases in subjects with diabetes was higher in contrast to non-diabetic subjects. No gender-wise variation was found. The majority of the patients had a period of diabetes between 5 and 10 years. Hypertension was common in both the groups that are type 2 diabetic and nondiabetic. Conclusion: Chronic kidney diseases are highly frequent in diabetic patients. There is a need to deal with hypertension, increased BMI, and weight.